Optical and Morphological Studies of Thermally Evaporated PTCDI-C8 Thin Films for Organic Solar Cell Applications - Ronak Rahimi; V. Narang; D. Korakakis (International Journal of Photoenergy)
PTCDI-C8 due to its relatively high photosensitivity and high electron mobility has attracted much attention in organic semiconductor devices. In this work, thin films of PTCDI-C8 with different thicknesses were deposited on silicon substrates with native silicon dioxide using a vacuum thermal evaporator. Several material characterization techniques have been utilized to evaluate the structure, morphology, and optical properties of these films. Their optical constants (refractive index and extinction coefficient) have been extracted from the spectroscopic ellipsometry (SE). X-ray reflectivity (XRR) and atomic force microscopy (AFM) were employed to determine the morphology and structure as well as the thickness and roughness of the PTCDI-C8 thin films. These films revealed a high degree of structural ordering within the layers. All the experimental measurements were performed under ambient conditions. PTCDI-C8 films have shown to endure ambient condition which allows pots-deposition characterization.